Pengaruh Komunikasi Organisasi Terhadap Motivasi Kerja Guru - Patappa, Maghfira Maulani; Sogalrey, Febi Adriana Mutiara (NOKEN : Jurnal Pengelolaan Pendidikan, 2024)
This research aims to find out how organizational communication influences teacher work motivation. This research is descriptive research using associative methods which aims to determine the influence of organizational communication on the work motivation of State Middle School teachers in Masamba District, North Luwu Regency. The sample in this research consisted of 60 teachers. The sample was determined using proportional random sampling technique. The data collection technique used a questionnaire instrument, and the questionnaire data were analyzed using a descriptive statistical approach and tested using a simple correlation formula, T test and F test. The results of the research showed that: There is a positive influence between organizational communication on teacher work motivation.